THE SOURCE AND ORIGIN OF TERRIGENOUS SEDIMENTARY ROCKS IN THE MESOPROTEROZOIC UI GROUP, SOUTHEASTERN RUSSIA - Cullers R.L.; Podkovyrov V.N. (My University, 2002)
Arenites, wackes, and associated shales and siltstones of the Ui group of Riphcan age in southeastern Siberia have been analyzed for petrographic, major element and selected trace element compositions (including the REE). Petrographic results suggest that the arenites may have been derived from granites and that the wackes may have been derived from more plagioclase-rich rocks like tonalites or granodiorites. The high quartz relative to other materials in many sandstones suggest that they may have been derived from intense chemical weathering or diagenesis so the mineralogic ratios may have been changed during these processes. The shales and siltstones are composed mostly of illite and quartz. In addition, A–CN–K diagrams indicate that the wackes and associated shales and siltstones underwent K-metasomatisim. Extrapolation of the shales and siltstones associated with the wackes back to the plagioclase–alkali feldspar line in the A–CN–K diagram suggests a high average plagioclase to alkali feldspar ratio in the provenance (tonalite to granodiorite). Extrapolation of shales and siltstones associated with the arenites suggest a low plagioclase to alkali feldspar ratio in the provenance (granite). In addition, the index of compositional variability (ICV) and chemical index of alteration (CIA) parameters of the shales and siltstones suggest the weathering of the first cycle material was intense. Trace element ratios suggest all the sedimentary rocks were derived from mostly granitoids. Shales and siltstones were plotted as elemental ratios (e.g. Th/Sc vs. Eu/Eu*). These plots suggest a mix of a granodiorite–tonalite source (for the source of the shales and siltstones associated with the wackes) with a granite source (for the shales and siltstones associated with the arenites). The arenites also contain lower Eu/Eu* and higher Th/Co and Th/Sc ratios than the wackes. This, as is consistent with the petrography, suggests that the arenites were derived from a source with more granite and less granodiorite–tonalite than the wackes.
Keywords: Sandstones; Shales; Provenance; Trace elements; REE; Mesoproterozoic; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская